How Undergraduate Students Perceive the Relevance of Open Source Software Literature - Machado, Michelangelo da R.; Cardoso, Cristiane Naves; Canedo, Edna Dias (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
The number of Open Source Software research papers has grown significantly over the last few years. An important open question is related with the investigation of how undergraduate students perceive the relevance of open source software literature. To address this question, we conducted a survey at University of Brasília (UnB) where 500 undergraduate students were invited to rate the relevance of research ideas contained in papers that were published over a period of ten years. This paper attempts to investigate whether the Open Source Software research produces results considered relevant to undergraduate students. This way we can provide feedback from the students, offering a way to produce useful and, consequently, more disseminated works among Open Source practitioners. To answer about the relevance of available work, we have tackled two questions: one about the scope of the studies and another about the quality perceived by them. For the first one, a systematic mapping was conducted, revealing a set of works composed by a great diversity of results. Than, we applied a Survey in which students could evaluate the relevance of these gathered works. The available open source software research works seem to be very diverse and were considered useful for students that contribute to the Open Source Projects. 77.01% of respondents answered that research conducted in the Open Source Community is relevant and important to the community, as well as to their professional and academic lives.